ANALYSIS OF FAULT CHARACTERISTIC AS HIDROCARBON TRAP IN KIRI TROUGH - CENTRAL SUMATRA BASIN - Hesty Widyastini (NIM 220 05 024), Irma
Abstract : Kiri Trough is located in the western part of Central Sumatra Basin. It is bounded by N-S trending ramp flat ramp normal fault in the west. During detail mapping of the Paleogene interval, syn-rift structure evaluation of this trough especially around Kelabu-Jingga Fields was approached with a structure concept which is extensional regime of F1 normal faulting. It is different with the previous interpretation where was applied on compressional regime of F1L/F2E strike slip system. It was interpreted previously that the anticline formed the Kelabu-Jingga fields is a pop-up structure of positive flower structure. But by detail mapping and 2D seismic restoration, it could be recognized clearly that the structure is formed by normal fault on a specific basement condition. The basement cut by the normal fault has high and flat area below Jingga field. Therefore it formed a ramp flat ramp normal faulting system. Flat area caused folding of syn-rift strata above the basement during F1. Finally Kelabu-Jingga trapping system is formed by the fold and some smaller scale normal faults cut the anticline during the folding and formed crestal collapse graben. This interpretation could be traced on the 2D seismic data from the north to the south. Finally syn-rift structure will influence the trough configuration and the distribution of sediment accumulation which is form syn-rift deposit.